KESENJANGAN KEPUASAN PEMIRSA TELEVISI PADA PROGRAM SERIAL DRAMA INDIA â€œGOPIâ€ DI ANTV DAN â€œGANGAA SEASON 2â€ DI SCTV (STUDI KASUS PADA WARGA TAMBAKSARI SELATAN RT. 02 SURABAYA) - Aini, Nurul; Darmawan, Arif; Putri, Sukma Ari Ragil (representamen, 2018)
The Indian Drama series is one of the television programming that is now thefocus of television viewers. ANTV can be regarded as a pioneer television station theemergence of Indian drama series. SCTV also took part in broadcasting an Indian dramaseries program. Two Indian drama series that have aired simultaneously on twotelevision stations are Gopi in ANTV and Gangaa Season 2 on SCTV. From the existenceof the problem, the researcher wanted to know how big the satisfaction expected, thesatisfaction obtained, and the gap of satisfaction in the drama series of India Gopi inANTV and Gangaa Season 2 in SCTV. This research uses using and gratifications theoryby using data analysis of Palmgreen discrepancy, which is used to know the gap ofsatisfaction. The results show that in general the Indian Gopi drama series in ANTV issuperior to Gangaa Season 2 in SCTV, as evidenced by 13 types of needs, Gopi issuperior with 11 types of needs with the highest percentage of which is included in thehigh category of 91.23%. While Gangaa Season 2 is only able to give satisfaction to therespondents as many as 10 types of needs, with the largest percentage included in themedium category, namely 87.72%.Keywords: Satisfaction Gap, Indian Drama Series.